Developing Self Aggression for Student: A Measurement Scale - Putera, I Made Riki Prabawa; Dharsana, I Ketut; Suranata, Kadek (Department of Guidance and Counseling, FIP, Undiksha, 2020)
The purpose of this development is to produce instruments of self-aggressiveness assessment instruments for students, valid and reliable. The method used is research and development is a research method used to produce certain products, and test the effectiveness of these products. The 4D model research and development model consists of 4 stages, namely; define, design, develop and disseminate. In this study, validation was carried out by 5 experts consisting of 3 Undiksha Counseling Postgraduate lecturers and 2 BK counselors. The results of the calculation of the CVR instrument of self-aggression with 30 statements get results more than 0 (> 0), which means 30 items are declared valid instruments. Furthermore, an analysis of CVI data with results of 0.58 or CVI of more than 0, then the questionnaire instrument was declared valid. After calculating the reliability value (r11) the self-aggressiveness instrument is 0.931 with a very high reliability category.